Evaluation of shear bond strength at the interface of two porcelains and pure titanium injected into the casting mold at three different temperatures - Bondioli, D. R.; Bottino, M. A. (Mosby, Inc, 2004)
Statement of problem. Titanium has physical and mechanical properties, which have led to its increased use in dental prostheses despite casting difficulties due to high melting point and formation of oxide layers which affect the metal-ceramic bond strength.Purpose. This in vitro study evaluated the shear bond strength of the interface of 2 dental porcelains and pure titanium injected into a mold at 3 different temperatures.Material and methods. Using commercially pure (cp) titanium bars (Titanium, Grade I) melted at 1668degreesC and cast at mold temperatures of 430degreesC, 700degreesC or 900degreesC, 60 specimens were machined to 4 x 4 mm, with a base of 5 x 1 mm. The 4-mm surfaces were airborne-particle abraded with 100 mum aluminum oxide before applying and firing the bonding agent and evaluating the 2 porcelains (Triceram/Triline ti and Vita Titankeramik). Ten specimens were prepared for each temperature and porcelain combination Shear bond testing was performed in a universal testing machine, with a 500-kg load cell and crosshead speed of 0.5 mm/min. The specimens were loaded until failure. The interfaces of representative fractured specimens of each temperature were examined with a scanning electron microscope (SEM) and energy dispersive spectrometer (EDS). Data for shear bond strength (MPa) were statistically analyzed by 2-way ANOVA and the Tukey test (alpha = .05).Results. The results showed significant differences for the metal/porcelain interaction effect (P = .0464). There were no significant differences for the 2 porcelains (P = .4250). The Tukey test showed a significant difference between the pair cp Ti 430degreesC Triceram and cp Ti 900degreesC Triceram, with respective mean values and SDs of 59.74 +/- 11.62 and 34.03 +/- 10.35 MPa.Conclusion. Triceram porcelain showed a bond strength decrease with an increase in the mold temperature for casting titanium. The highest bond strength for Vita porcelain and the best metal-ceramic interface observed with the SEM were found with the mold temperature of 700degreesC.